COFFEE LEAF MINER INCIDENCE AND ITS PREDATION BY WASP IN COFFEE INTERCROPPED WITH RUBBER TREES - Androcioli, Humberto Godoy; Hoshino, Adriano Thibes; Menezes Júnior, Ayres de Oliveira; Morais, Heverly; Bianco, Rodolfo; Caramori, Paulo Henrique (Coffee Science - ISSN 1984-3909, 2018)
The coffee leaf miner (CLM) Leucoptera coffeella has a wide distribution and causes significant losses in coffee plantations (Coffea spp.) in Brazil. Its occurrence can be mitigated in intercropped systems, with the rubber tree (Hevea brasiliensis) adapting well to the consortium, while also providing extra income to the producer. We aimed to determine whether the afforestation influences the microclimate and affects the leaf miner incidence and its predation by wasp in coffee plants intercropped with rubber trees. The study was undertaken in state of Paraná, Brazil, using coffee plants intercropped with rubber trees planted in double rows (alleys) spaced at 13, 16 and 22 m between alleys, and compared to sole cropping coffee plots. From January 2008 to November 2010, the presence of CLM’s lesions including those with signs of wasp predation was monitored in coffee plants intercropped with rubber trees and in the non-consorted coffee. A higher CLM’s incidence was verified in monoculture coffee plots, while coffee plants located under and two meters away from rubber trees had the lowest incidences. CLM’s incidence in intercropping system got higher as it increased distance from the trees. The number of lesions with signs of predation by wasps was positively correlated with the number CLM’s lesions, indicating a density-dependent predator-prey relationship. The coffee plants intercropped with alley rubber trees reduce the CLM’s occurrence and can be a management’s tactic for this economically important pest.